الهيمنة الحضارية ودورها في نشر العقيدة: دراسة في ضوء التاريخ الاسلامي - Zia al-Haq; Abdul Qadir Haroon (الآفاق اسلامی و تحقیقی مجلہ, 2022)
Historians consider Islam to be one of the world's youngest religions, having emerged in the early seventh century. Within a century the early Muslims established an empire that stretched from modern-day Spain to India in the east. Many of the conquered peoples eventually converted to Islam, laying the groundwork for today's global Muslim community, widely regarded as the world's second-largest and fastest-growing religion. No other religion in the world has spread as quickly as Islam. Some scholars attribute the quick emergence of the Islamic message to the geographical and geo-historical setting of Arabian Peninsula. Others believe that Islam is imposed on people by force, while another group of scholars believes that the veracity of the Islamic message inspired people to accept it of their own free will and conviction. They entirely negate the role of Islamic political dominance in spreading the Islamic message. Using an analytical approach, we argue in this article that, while Islam is not forced on people, it is clear that Islamic civilizational dominance played a significant role in the spread of the Islamic Message. It is concluded that throughout history, political and civilizational factors have always played an indirect role in the spread of cultural and religious values, and Islam is no exception in this regard...